Environmental and Genetic Traffic in the Journey from Sperm to Offspring - Sengupta, Pallav; Dutta, Sulagna; Liew, Fong Fong; Dhawan, Vidhu; Das, Biprojit; Mottola, Filomena; Sláma, Petr; Rocco, Lucia; Roychoudhury, Shubhadeep (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2023)
Recent advancements in the understanding of how sperm develop into offspring have shown complex interactions between environmental influences and genetic factors. The past decade, marked by a research surge, has not only highlighted the profound impact of paternal contributions on fertility and reproductive outcomes but also revolutionized our comprehension by unveiling how parental factors sculpt traits in successive generations through mechanisms that extend beyond traditional inheritance patterns. Studies have shown that offspring are more susceptible to environmental factors, especially during critical phases of growth. While these factors are broadly detrimental to health, their effects are especially acute during these periods. Moving beyond the immutable nature of the genome, the epigenetic profile of cells emerges as a dynamic architecture. This flexibility renders it susceptible to environmental disruptions. The primary objective of this review is to shed light on the diverse processes through which environmental agents affect male reproductive capacity. Additionally, it explores the consequences of paternal environmental interactions, demonstrating how interactions can reverberate in the offspring. It encompasses direct genetic changes as well as a broad spectrum of epigenetic adaptations. By consolidating current empirically supported research, it offers an exhaustive perspective on the interwoven trajectories of the environment, genetics, and epigenetics in the elaborate transition from sperm to offspring.
Keywords: genetic infertility; epigenetic changes; transgenerational effects; semen quality; environmental pollution